Corporate governance and dividend policy in the presence of controlling shareholders - Ricardo Rodrigues; J. Augusto Felício; Pedro Verga Matos (Journal of Risk and Financial Management, 2020)
Based on agency theory, we focused on the influence of corporate governance in the dividend policy of large listed firms with headquarters in continental Europe countries. Previous research focused on the influence of corporate governance on the performance and risk of listed firms, but the influence of corporate governance on the dividend policy has rarely been addressed despite the importance of dividends for shareholders and the implications on the free cash-flow, whose application may be a source of conflicts between managers and shareholders. In this paper, we study the influence of a set of governance mechanisms on the dividend policy over 12 years (2002 to 2013). The results, based on a panel data analysis, support the importance of governance mechanisms toward the protection of shareholders' interests, and reveal that the decisions on whether to pay dividends and how much to pay are grounded on different antecedents.
Keywords: 330; corporate governance; agency theory; dividend policy